As práticas pedagógicas em uma escola pública paranaense: o ensino de ciências com base nos parâmetros curriculares nacionais - Domareski, Irene (2011)
This dissertation aims to research the pedagogical practices of teachers of natural sciences from the National Curriculum in Public School Jose de Anchieta - elementary and high school of Quedas do Iguaçu, Parana. For this procedure, the field research made use of analysis of official documents of the school, of consultations of didactic plans (prepared by teachers of Sciences), of textbooks used in school and science´s notebooks of some students of this school. Books daily class which indicates the presence of students, notes on the evaluation process, as well as pedagogical practices held served as a reference source by teachers in the bimesters. For greater accuracy of the information contained in this document, the research also drew on the responses of the questionnaire and the interviews that were presented to teachers.To better understand the object of analysis, this work has broadened its scope over the focus of literature, images and pictures, to compose a historical overview of education in Brazil with the development aspects of the teaching of Natural Sciences. Aiming to better situate the research institution, we designed a rescue of the socio-historical development of the city of Quedas do Iguaçu. Through the study, these results allowed the following conclusion: teachers know little of the research institution of didactic propositions contained in the National Curriculum. This document is not a source on the educational development of their actions. The pedagogical practices that are developed by teachers follow in part the guidelines present in the Science Curriculum Guidelines for Elementary Education of the State of Parana.